2019
DOI: 10.1186/s40644-019-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

High negative predictive value of 68Ga PSMA PET-CT for local lymph node metastases in high risk primary prostate cancer with histopathological correlation

Abstract: BackgroundCurrent guidelines highlight the importance of accurate staging in the management and prognostication of high risk primary prostate cancer. Conventional radiologic imaging techniques are insufficient to reliably detect lymph node metastases in prostate cancer. Despite promising results, there is limited published data on the diagnostic accuracy of PSMA PET-CT to assess local nodal metastases prior to radical prostatectomy.This study aims to assess the diagnostic efficacy of 68Ga PSMA PET-CT in local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…PSMA is a membrane-bound enzyme with high expression in prostate cancer cells and low expression in benign prostatic tissue [ 3 ]. Over the past few years, targeted imaging of PSMA has been used in various clinical managements, such as imaging-guided biopsy, staging of primary tumor, localization of biochemical relapse, planning of radiotherapy, prediction and assessment of tumor response to systemic therapy [ 4 7 ]. The PSMA expression level of PCa and tumor level, Gleason score and PSA stage before treatment have been proved definitely correlated, and the expression levels have been found to be a predictor for PCa progression [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…PSMA is a membrane-bound enzyme with high expression in prostate cancer cells and low expression in benign prostatic tissue [ 3 ]. Over the past few years, targeted imaging of PSMA has been used in various clinical managements, such as imaging-guided biopsy, staging of primary tumor, localization of biochemical relapse, planning of radiotherapy, prediction and assessment of tumor response to systemic therapy [ 4 7 ]. The PSMA expression level of PCa and tumor level, Gleason score and PSA stage before treatment have been proved definitely correlated, and the expression levels have been found to be a predictor for PCa progression [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…American Society of Clinical Oncology (ASCO) guidelines recommend the use of NGIs in the evaluation of high-risk locally advanced prostate cancer, in which conventional imaging is negative, indeterminate or suspicious 14 . A number of studies [15][16][17][18][19] have shown that PSMA-PET outperforms conventional imaging in identifying nodal and metastatic bone disease, with up to 27% greater diagnostic accuracy (92% [88][89][90][91][92][93][94][95] versus 65% [60][61][62][63][64][65][66][67][68][69]; p<0•0001) compared with conventional CT and bone scan. In a 2020 systematic review including 18 trials and 969 patients assessing PSMA PET for primary lymph node staging 18 , the weighted sensitivity, weighted specificity and positive predictive values were 59%, 93% and 20-100% (greater than 80% in the majority of trials), respectively (compared with 42%, 82% and 32% for CT).…”
Section: [H2]newly Diagnosed High-risk Diseasementioning
confidence: 99%
“…Although PSMA PET is approved in an increasing number of settings 156 , the research on its use focuses heavily on the diagnostic accuracy of the modality. PSMA PET has been shown to be more sensitive than conventional imaging and PSMA-avid lesions can be detected at very low PSA levels [15][16][17][18][19] .This discrepancy between imaging techniques can result in stage migration and a subsequent change in management plan for that patient. However, a change in management plan has not been demonstrated to translate to an increase in disease-free survival or overall survival.…”
Section: [H2]differential Diagnosis Of Findingsmentioning
confidence: 99%
“…Reasons for exclusion were most often a reference standard inappropriate for the review question or patient-based data only. Other reasons for exclusion were insufficient data to extract required accuracy measures, [44][45][46][47] too few patients, [48][49][50][51][52][53][54] or study objective and design outside scope of the review. [55][56][57][58][59][60][61][62][63][64][65][66][67] Finally, a total of 34 studies were included.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%